PRE-SERVICE ELEMENTARY SCHOOL TEACHERS’ MATHEMATICS ANXIETY AND MATHEMATICS SELF-EFFICACY AND THEIR RELATIONSHIP TO MATHEMATICAL TEACHING PERFORMANCE - Osman ÇİL (International Journal of Eurasia Social Sciences, 2017)
Mathematics anxiety is a common phenomenon in a very competitive age that makes demands on individuals to exhibit their mathematical competence. Preparing pre-service teachers to effectively teach mathematics is repeatedly suggested as one way to decrease or prevent the negative effects of mathematics anxiety on elementary school students, since studies frequently portray elementary school teaching majors as having higher mathematics anxiety than other teaching majors. The aim of this quantitative study was to investigate the differences between pre-service elementary teachers’ mathematics anxiety and mathematics teaching self-efficacy, based on their performance in a mathematics teaching method course. The data analysis revealed that pre-service teachers with high mathematics anxiety achieved lower scores and developed less self-efficacy than pre-service elementary teachers with low mathematics anxiety. There was also a statistically significant negative relationship between pre-service teachers’ mathematics anxiety and their mathematics teaching self-efficacy.